Encyclopedia of percussion - Beck, John H. 1933- (2014)
"Percussion: An Encyclopedia, 2nd edition, updates and enlarges one of Routledge's most successful music-reference works. The only comprehensive encyclopedia covering all of the major percussion instruments, the volume is divided into 4 major sections: an alphabetical dictionary of percussion instruments and terms; illustrations of key percussion instruments; longer, individual articles on key members of the percussion family, from Bass Drum to Xylophone, written by leading percussionists and scholars; and finally, several appendices of terms and symbols and a comprehensive bibliography. This new edition is expanded to include new research in the field as well as increased coverage of electronic and world percussion instruments."--Publisher description